Fat Taste Sensitivity Is Associated with Short-Term and Habitual Fat Intake - Costanzo, Andrew (Nutrients, 2017)
Evidence suggests individuals less sensitive to fat taste (high fat taste thresholds (FTT)) may be overweight or obese and consume greater amounts of dietary fat than more sensitive individuals. The aims of this study were to assess associations between FTT, anthropometric measurements, fat intake, and liking of fatty foods. FTT was assessed in 69 Australian females (mean age 41.3 (15.6) (SD) years and mean body mass index 26.3 (5.7) kg/m(2)) by a 3-alternate forced choice methodology and transformed to an ordinal scale (FT rank). Food liking was assessed by hedonic ratings of high-fat and reduced-fat foods, and a 24-h food recall and food frequency questionnaire was completed. Linear mixed regression models were fitted. FT rank was associated with dietary % energy from fat ([Formula: see text] = 0.110 [95% CI: 0.003, 0.216]), % energy from carbohydrate ([Formula: see text] = −0.112 [−0.188, −0.035]), and frequency of consumption of foods per day from food groups: high-fat dairy ([Formula: see text] = 1.091 [0.106, 2.242]), meat & meat alternatives ([Formula: see text] = 0.669 [0.168, 1.170]), and grain & cereals ([Formula: see text] = 0.771 [0.212, 1.329]) (adjusted for energy and age). There were no associations between FT rank and anthropometric measurements or hedonic ratings. Therefore, fat taste sensitivity appears to be associated with short-term fat intake, but not body size in this group of females.